Developing and testing a brief clinic‐based lung cancer screening decision aid for primary care settings. (23rd February 2018) - McDonnell, Karen Kane; Strayer, Scott M.; Sercy, Erica; Campbell, Callie; Friedman, Daniela B.; Cartmell, Kathleen B.; Eberth, Jan M.
Abstract: Background: Cancer screening‐related decisions require patients to evaluate complex medical information in short time frames, often with primary care providers (PCPs) they do not know. PCPs play an essential role in facilitating comprehensive shared decision making (SDM). Objective: To develop and test a decision aid (DA) and SDM strategy for PCPs and high‐risk patients. Design: The DA was tested with 20 dyads. Each dyad consisted of one PCP and one patient eligible for screening. A prospective, one‐group, mixed‐method study design measured fidelity, patient values, screening intention, acceptability and satisfaction. Results: Four PCPs and 20 patients were recruited from an urban academic medical centre. Most patients were female (n = 14, 70%), most had completed high school (n = 15, 75%), and their average age was 65 years old. Half were African American. Patients and PCPs rated the DA as helpful, easy to read and use and acceptable in terms of time frame (observed t  = 11.6 minutes, SD 2.7). Most patients (n = 16, 80%) indicated their intent to be screened. PCPs recommended screening for most patients (n = 17, 85%). Conclusions: Evidence supports the value of lung cancer screening with LDCT for select high‐risk patients. Guidelines endorse engaging patients and their PCPs in SDM discussions. Our findings suggest that using a brief, interactive, plain‐language, culturally sensitive, theory‐based DA and SDM strategy is feasible, acceptable and may be essential to effectively translate and sustain the adoption of LDCT screening recommendations into the clinic setting.